BACTERIOLOGICAL ANALYSIS OF UNTREATED RETAIL RAW MILK COLLECTED FROM RANDOM SUPPLIERS AT DOHUK GOVERNORATE – KURDISTAN REGION – IRAQ - Issa, Fawzi A.; Khidhir, Mohammed A. (Science Journal of University of Zakho, 2023)
Milk is a high nutritional food and extremely sensitive to bacterial contamination. The current study aimed to assess the presence and density of bacteria in local raw milk. Eighty raw milk samples were collected from four distanced geographical locations at Dohuk Governorate, Kurdistan Region-Iraq. For each geographical site, two private farms were randomly chosen for collecting milk samples. A batch of 10 raw milk samples was obtained from each farm for bacterial availability analysis. All samples were incubated with aeration at 37 °C for 24-48h on specific bacteriological media. Aerobic bacteria were observed in all sheep raw milk samples. The mean counts of total aerobic bacterial in samples from all farms were from 1.0 x 104 to more than 3.0 x 106 cfu/mL. Staphylococcus aureus was found in 37.5% (n=30); 50% (n=10); for B, D, and K groups, no S. aureus was observed in Z group. S. aureus density was from 1 x 103 to 4.0 x 104 cfu/mL (B Group); 2.7 x 104 to 3.0 x 104 cfu/mL (D Group); and 2.7 x 104 to 3.0 x 104 cfu/mL (K group). Escherichia coli was found in 23.75% (n=19); 40% (n=8), 50% (n=10), and 5% (n=1) of the raw milk samples for B, D, and K groups respectively as Z group was free of E. coli. E. coli contaminated samples produced bacterial growth from 6.0 x 103 to 7.6 x 104 cfu/mL (B Group); and 1.0 x 103 to 6.0 x 103 cfu/mL (D group) and only one sample from K group was contaminated with E. coli (7.4 x 104 cfu/mL). Klebsiella spp were observed in 57.5% (n=46) of the raw-milk samples; Z group 40% (n=8), B group 80% (n=16), D group 50% (n=10), and K group 60% (n =12). Bacterial abundance was from 2.6 x 104 to 1.88 x 105 cfu/mL (Z group); 1.3 x 104 to 1.51 x 105 cfu/mL (B group); 6.0 x 103 to 1.8 x 104 cfu/mL (D group); and from 2.4 x 105 to 1.24 x 106 cfu/mL (K group). Shigella raw milk positive samples were observed in 48.75% (n=39); Z group 100% (n=20), B group 45% (n=9), D group 50% (n=10), while K group was free of Shigella spp. Bacterial density was from 1.9 x 104 to 2.37 x 105 cfu/ mL (Z group), from 5.0 x 103 to 4.8 x 104 cfu/ mL (B group), and from 5.0 x 103 to 2.3 x104 (D group). All sheep raw-milk samples of this work were completely free of any species of Salmonella rods. However, 72 out of 80 examined samples of this study exceeded the total aerobic bacterial count according to the European recommended standards. Good hygienic practices, transporting milk in cold and clean containers, and regular medical checkup for sheep are suggested.